Norway : Financial Sector Assessment Program. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses key findings and recommendations of the Financial System Stability Assessment for Norway. Norway's financial system coped well with the global financial crisis and has further increased buffers to deal with potential shocks, but significant financial imbalances have also built up since then. Stress tests suggest that under severe macroeconomic shocks, banks and life insurers could face important but manageable capital shortfalls. The authorities have taken significant measures to improve the oversight framework, but further strengthening is needed. The regulatory and supervisory framework is generally good, but some weaknesses need to be addressed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet